The Removal of the Constitutional Chamber Justices in El Salvador: A Story About the Fragility of Judicial Independence - Manuel Adrián Merino Menjívar (The Constitutional Court of the Republic of Indonesia, 2024)
The work discusses a significant event that occurred on May 1, 2021, when the Legislative Assembly of El Salvador removed the Justices of the Constitutional Chamber of the Supreme Court of Justice before their term expiration, violating legal procedures. This action was facilitated by a combination of populist rhetoric from the President and abuse of power by the Legislative Assembly. Referred to as Constitutional Authoritarian-Populism, this trend undermines the rule of law. The text outlines the Salvadoran constitutional framework and discusses concepts like judicial independence, populism, abusive constitutionalism, and authoritarianism in the Latin American context. It then examines instances of Constitutional Authoritarian-Populism in El Salvador from 2019 to 2023, demonstrating that the removal of the Justices wasn’t spontaneous. Finally, it analyzes the process of removal, the response from the removed Justices, and the subsequent decision by newly appointed Justices to authorize presidential re-election in El Salvador.